2018
DOI: 10.1080/10803548.2018.1514135
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward elderly workers and perceptions of integrated age management practices

Abstract: This qualitative study investigates attitudes toward elderly workers and their work situation in different sectors, and explores perceptions and organizational measures that can enable an extended working life. Previous age management studies indicate that there are several interconnected measures and key areas of importance, and that there is a general need for strategies to strengthen sustainable age management at the organizational level. A structured content analysis was used to analyze data from focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…The Nordic welfare states have been described as some of the world's most generous (Esping-Andersen 1990), and Salomon makes the claim that attitudes towards older workers seem to be more positive in the Nordic countries 'compared with several countries in Southern and Eastern Europe ' (2012, p. 2). In both the Nordic and other countries however, managers seem reluctant to hire applicants in their late 50s (Blomé et al 2018;Conen et al 2012;Solem 2016).…”
mentioning
confidence: 99%
“…The Nordic welfare states have been described as some of the world's most generous (Esping-Andersen 1990), and Salomon makes the claim that attitudes towards older workers seem to be more positive in the Nordic countries 'compared with several countries in Southern and Eastern Europe ' (2012, p. 2). In both the Nordic and other countries however, managers seem reluctant to hire applicants in their late 50s (Blomé et al 2018;Conen et al 2012;Solem 2016).…”
mentioning
confidence: 99%
“…Age management can play its role both for individuals, organisations and the state as stakeholders, as confirmed by [78,79]. In accordance with the results of [73,74,[76][77][78]80] it is necessary to transform both system of education and retraining and, at the same time, to transform the approach of age management to age 50+ employees at the organisation level. Author [81] states that care for sustainability of older workers, which was stressed by [77], is needed because unrealised, deliberate and emerging strategies according to [81,82] are performed by age managements such.…”
Section: Discussionmentioning
confidence: 60%
“…An examination of the interdependence of the relationship between access to education, educational objectives, educational structure and increasing age of workers confirmed that older workers have a stronger and more positive attitude towards their development [75]. The study of [76] focuses on older workers' access to workload and their work situation across different sectors. The aim of the research was primarily to describe the perception and attitudes of organisations to prolong working life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good interplay between the worker and the working environment, taking the workers' capacities and the work requirements into account to attain a good balance between individual resources and work demands, is needed for sustainable employment (54). To meet real problems faced by workers and employers, positive examples must be emphasized and negative patterns decreased (52). Although age management is not aimed towards a certain age group, addressing the needs of ageing workers could help employers in the health care sector deal with the lack of skilled workers, and in turn receive more workers with better well-being, better work ability and possibly longer careers (33).…”
Section: Discussionmentioning
confidence: 99%